Building a Positive Relationship Between Teachers and Students - Ode Yahyu Herliany Yusuf; Nur Hidayati; Ferliani Ferliani; Sukarni Sukarni; Zainab Zainab (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The purpose of this study is to find out educators in building positive relationships between teachers and students in the learning process. Educators are also invited to be more aware of the importance of a positive relationship between educators and students and how to initiate positive interactions during the learning process. This research is a library research. Data sources are books and electronic scientific articles. The data collection technique is to search for data online through the Google Scholar database. Meanwhile, data analysis in this study used content analysis. The results of this study show that an educator regarding teacher and student relationships can improve, and educators can determine the right plan that can be carried out.